VD_FINDINFO HC / 2009 / 479 vom 5. Oktober 2009 - VD Tribunal cantonal (2009)
COMPÉTENCE RATIONE LOCI, FIXATION DE LA PEINE | 47 CP, 411 let. a CPP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 415 CPP